Low Serum High-density Lipoprotein Cholesterol in Childhood is Associated with Adolescent Asthma - Yiallouros, Panayiotis K.; Savva, Savvas C.; Kourides, Yiannis; Kolokotroni, Ourania; Behbod, Behrooz; Zeniou, Maria; Economou, Mary; Chadjigeorgiou, Charalambos; Lamnisos, Demetris; Middleton, Nicos; Milton, Donald Kirby; Tornaritis, Michael J. (My University, 2012)
Background Whilst emerging evidence from animal and cell experiments has shown high‐density lipoprotein cholesterol to have anti‐inflammatory effects consistent with a protective role in asthma, human studies investigating the relationship of high‐density lipoprotein cholesterol with asthma have produced conflicting results. Objective To examine the association between serum lipids among Cypriot children aged 11–12 years and prevalence of asthma at age 15–17 years. Methods In 3982 children, we assessed serum lipids, body mass index and maximal oxygen consumption at baseline (2001–2003) and explored associations with respiratory health at follow‐up (2007) using multiple logistic regression models. Results Lower levels of high‐density lipoprotein cholesterol at age 11–12 years were found in subjects who reported ever asthma (58.2 vs. 60.0 mg/dL, P = 0.005) and active asthma (57.5 vs. 59.9 mg/dL, P = 0.010) in adolescence, in comparison with their respective reference groups. Total cholesterol, low‐density lipoprotein and triglycerides had no association with any of the asthma outcomes. In contrast, with estimated odds ratios of 1.89 (95% CI 1.19–3.00) and 1.89 (95% CI 1.02–3.53), ever asthma and active asthma respectively appeared particularly pronounced among those who at baseline had high‐density lipoprotein cholesterol <40 mg/dL, even after adjusting for potential confounders including body mass index and maximal oxygen consumption. Conclusions & Clinical Relevance Low‐serum high‐density lipoprotein cholesterol in childhood is associated with an increased risk for asthma in adolescence, suggesting a potential role of this lipoprotein in the pathogenesis of paediatric asthma.
Keywords: Adiposity; Adolescents; Asthma; High-density lipoprotein cholesterol; Physical fitness